anonymous
  • anonymous
f(x) =(x/8)-3, g(x)=x^3 (f*g)^-1=
Mathematics
  • Stacey Warren - Expert brainly.com
Hey! We 've verified this expert answer for you, click below to unlock the details :)
SOLVED
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
schrodinger
  • schrodinger
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
anonymous
  • anonymous
is that composite functions? \[(fog)\]
anonymous
  • anonymous
yes
anonymous
  • anonymous
pretty much substitute g(x) into the x of f(x)

Looking for something else?

Not the answer you are looking for? Search for more explanations.

More answers

anonymous
  • anonymous
f(g(x))
anonymous
  • anonymous
yeah but i got (x^(1/3)/8)-3
anonymous
  • anonymous
is \[f(x)=\frac{ x }{ 8 }-3\]?
anonymous
  • anonymous
yes
anonymous
  • anonymous
\[(fog)=\frac{ x^3 }{ 8 }-3\]
anonymous
  • anonymous
just plug x ==> x^3
anonymous
  • anonymous
it said it was wrong
anonymous
  • anonymous
@chris00
anonymous
  • anonymous
pic me the question
anonymous
  • anonymous
anonymous
  • anonymous
anonymous
  • anonymous
ohh inverse
anonymous
  • anonymous
\[y=f(x)=\frac{ x }{ 8 }-3\] y+3=x/8 8y+24=x then let x=y 8x+24=y=\[f(x)^{-1}\]
anonymous
  • anonymous
so \[f(x)^{-1}=8x+24\]
anonymous
  • anonymous
do the same for y=x^3
anonymous
  • anonymous
that would be x^1/3
anonymous
  • anonymous
y^(1/3)=x therefore \[g(x)^{-1}=x ^{1/3}\]
anonymous
  • anonymous
yep
anonymous
  • anonymous
now\[(fog)^{-1}=8x ^{1/3}+24\]
anonymous
  • anonymous
it says its wrong
anonymous
  • anonymous
lol werid
anonymous
  • anonymous
oh wait
anonymous
  • anonymous
( f o g)–1(x) = (g^–1 o f^ –1)(x)
anonymous
  • anonymous
so we sub f(x) into the x function of g
anonymous
  • anonymous
\[(fog)^{-1}=(8x+24)^{1/3}\]
anonymous
  • anonymous
try that
anonymous
  • anonymous
ah youre amazing!!!! thank you!!!!
anonymous
  • anonymous
:D
anonymous
  • anonymous
just try and know your properties. it a bit confusing http://www.purplemath.com/modules/fcncomp6.htm Thats a good link
anonymous
  • anonymous
will do, thanks!
anonymous
  • anonymous
: )

Looking for something else?

Not the answer you are looking for? Search for more explanations.